2017
DOI: 10.3389/fphys.2017.00092
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the CAchexia SCOre (CASCO). Staging Cancer Patients: The Use of miniCASCO as a Simplified Tool

Abstract: The CAchexia SCOre (CASCO) was described as a tool for the staging of cachectic cancer patients. The aim of this study is to show the metric properties of CASCO in order to classify cachectic cancer patients into three different groups, which are associated with a numerical scoring. The final aim was to clinically validate CASCO for its use in the classification of cachectic cancer patients in clinical practice. We carried out a case -control study that enrolled prospectively 186 cancer patients and 95 age-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 33 publications
(43 reference statements)
1
38
0
Order By: Relevance
“…It is for this reason that our research group introduced the so‐called CASCO (CAchexia SCOre), for assessing cancer patients. CASCO was recently validated . None of the published studies involving cancer cachexia experimental models include a measure of the severity of the syndrome like the previously reported CASCO system for human subjects .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is for this reason that our research group introduced the so‐called CASCO (CAchexia SCOre), for assessing cancer patients. CASCO was recently validated . None of the published studies involving cancer cachexia experimental models include a measure of the severity of the syndrome like the previously reported CASCO system for human subjects .…”
Section: Introductionmentioning
confidence: 99%
“…CASCO was recently validated . None of the published studies involving cancer cachexia experimental models include a measure of the severity of the syndrome like the previously reported CASCO system for human subjects . Therefore, the aim of the present investigation was to define and validate a cachexia score usable in both rats and mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Busquets et al . (University of Barcelona, Barcelona, Spain) present the development of an easy‐to‐use tool (CASC‐IN) for the evaluation of pre‐cachectic cancer patients . Using a population of 179 cancer patients, affected by a different tumour types, they showed that the frequencies observed are non‐cachectic: 58 (32.4%), pre‐cachectic: 7 (3.9%), and cachectic: 114 (63.7%).…”
Section: Body Compositionmentioning
confidence: 99%
“…Therefore, Busquets et al 43 (University of Barcelona, Barcelona, Spain) present the development of an easy-to-use tool (CASC-IN) for the evaluation of pre-cachectic cancer patients. 44,45 Using a population of 179 cancer patients, affected by a different tumour types, they showed that the frequencies observed are non-cachectic: 58 (32.4%), precachectic: 7 (3.9%), and cachectic: 114 (63.7%). They concluded that the CASC-IN not only permits the identification of those patients that are pre-cachectic but also serves to discriminate those patients that are cachectic and, therefore, can be included in staging determination by means of either CASCO or MiniCASCO.…”
Section: Body Compositionmentioning
confidence: 99%